Creating the effective primary school : a guide for school leaders and teachers - Smith, Roger, 1944- (Primary essentials series., 2002)
This practical and accessible handbook has been written by an experienced primary leader, and will offer anyone seeking guidance on creating or maintaining a more effective primary school a valuable and friendly resource.